The Effect Of Earnings Per Share, Return On Equity, And Net Profit Margin On Stock Returns Of Food Sub-Sector Companies and Beverages On Indonesia Stock Exchange - Nursidar, Nursidar; Budiyanti , Hetty; Nurman, Nurman; Anwar, Anwar; Musa , Muh. Ikhwan (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Indonesia's economy is largely driven by increasing household consumption and one of the fast-growing industries is the food and beverage industry. This study aims to test whether independent variables namely Earnings Per Share (EPS) X1, Return On Equity (ROE) X2, and Net Profit Margin (NPM) X3 affect Stock Return. The population in this study is 40 Food and Beverage Subsector companies located on the Indonesia Stock Exchange (IDX) for the 2014-2021 period, the sample used in this study is 13 companies selected by purposive sampling, and the data collection technique used is documentation. The data analysis techniques used are classical assumption tests, descriptive statistical tests, and hypothesis tests. The results of this study show that some Earning Per Share (EPS) have a negative effect on stock returns, Net Profit Margin (NPM) and Return On Equity (ROE) have a positive effect on stock returns, then simultaneously Earning Per Share (EPS), Return On Equity (ROE) and Net Profit Margin (NPM) have a significant effect on